A Silent Threat of Emerging Resistance Based on Antifungal Susceptibility Pattern of Filamentous Fungi by Microdilution, E Test and, Disc Diffusion Method: A Critical Constructive Analysis - Husain, Uneza; Priyadarshi, Ketan (Annals of the National Academy of Medical Sciences (India), 2022)
For more than two decades, antifungal susceptibility testing and interpretation haunted the medical professionals in diagnostics and management. This article mainly focuses on the three most widely used methods: broth microdilution, E test, and disc diffusion. It also focuses on the fact that clinicians should switch from empirical treatment to susceptible drugs as early as possible to combat antifungal resistance and newer mutations that horrify us every single day with poor patient outcomes. Many factors need to be taken into account during the interpretation of results but the positive side of the story is that they have been well documented in the literature. Though many methods have come up in testing antifungal susceptibility, still there is a scope for a rapid yet accurate testing modality to flourish and take the lead.
Keywords: filamentous fungi; broth microdilution; BMD; disc diffusion; E test